Social responsability in the municipality of Miraflores - Jáuregui Ramírez, Paola L. (2019)
For the new conceptions of sustainable cities, concepts have been generated that imply the complete, integrated and holistic development that can only be achieved through an integrationwith diverse elements and spheres.One very important is the social responsibility, that is the consciousness of the other from an ethical level and its respective practical application in the economic, social and cultural space.In the present work, we will analyze these standards in a municipality: Miraflores. Through a study of the services it provides and the way it does it, we will get closer to understanding if asustainable space is developed and that it respects and integrates the other.